When Unicorns Lie: Legal Perspectives on Accounting Fraud in The eFishery Startup Case - Lucky Elza Aditya; Fazal Akmal Musyarri (University of Merdeka Malang, 2025)
This study is intended to analyse the legal implications of financial statement fraud in the eFishery case, a prominent Indonesian aquaculture startup that achieved unicorn status. By employing a normative legal research method and case study analysis, this study investigates the modus operandi behind the alleged fraud, the violations of fiduciary and statutory duties, and the potential application of criminal liability. The need for this study is underscored by the rising complexity of startup ecosystems and the limited regulatory safeguards protecting investor and public interests. This study introduces a groundbreaking approach to examining digital corporate fraud by integrating legal doctrine with contemporary fraud theory, such as the Fraud Triangle. Our analysis reveals that the dual financial reporting system used by eFishery executives was a deliberate attempt to mislead stakeholders, violating multiple provisions under Indonesian corporate, financial, and criminal law. These findings are crucial as they demonstrate how current legal frameworks may be inadequate in addressing sophisticated fraud in tech-based startups. This study significantly advances our understanding of legal accountability in digital business models and provides policy insights for improving regulatory oversight. Penelitian ini bertujuan untuk menganalisis implikasi hukum dari pemalsuan laporan keuangan dalam kasus eFishery, sebuah startup akuakultur Indonesia yang telah meraih status unicorn. Dengan menggunakan metode penelitian hukum normatif dan pendekatan studi kasus, penelitian ini mengkaji modus operandi di balik dugaan fraud, pelanggaran terhadap kewajiban fidusia dan hukum, serta kemungkinan penerapan pertanggungjawaban pidana. Urgensi penelitian ini didasarkan pada kompleksitas ekosistem startup yang terus berkembang serta lemahnya perlindungan hukum terhadap kepentingan investor dan publik. Penelitian ini memperkenalkan pendekatan baru dalam menganalisis fraud korporasi digital dengan menggabungkan doktrin hukum dan teori fraud modern seperti Fraud Triangle. Hasil analisis menunjukkan bahwa sistem pelaporan keuangan ganda yang digunakan oleh eksekutif eFishery merupakan tindakan yang disengaja untuk menyesatkan para pemangku kepentingan, dan melanggar berbagai ketentuan dalam hukum perusahaan, keuangan, dan pidana Indonesia. Temuan ini penting karena mengungkapkan kelemahan kerangka hukum saat ini dalam menangani fraud kompleks di sektor startup teknologi. Penelitian ini berkontribusi secara signifikan dalam memperkuat pemahaman mengenai akuntabilitas hukum dalam model bisnis digital dan memberikan rekomendasi kebijakan untuk peningkatan pengawasan regulasi.